2004
DOI: 10.1038/sj.bjc.6601836
|View full text |Cite
|
Sign up to set email alerts
|

New technologies in screening for breast cancer: a systematic review of their accuracy

Abstract: We systematically reviewed the literature on the accuracy of new technologies proposed for breast cancer screening. Four potential tests were identified (ultrasound, magnetic resonance imaging (MRI), full-field digital mammography (FFDM), and computer-aided detection (CAD)) for which primary studies met quality and applicability criteria and provided adequate data on test accuracy. These technologies have been assessed in cross-sectional studies of test accuracy where the new test is compared to mammography. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 24 publications
(18 reference statements)
1
37
0
Order By: Relevance
“…Possibilities include more frequent screening or the introduction of alternative or additional screening modalities (such as ultrasound, magnetic resonance imaging, or digital mammography). Small studies on ultrasound and mammography together suggest that the addition of ultrasound improves sensitivity for women with dense breasts (20,21) but specificity is lower (22). The American College of Radiology Imaging Network study is conducting a randomized controlled trial of combined ultrasound and mammography for women classified by the Breast Imaging-Reporting and Data System classification as having heterogeneously dense or extremely dense breasts (approximately 40% of women ages z40 years; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Possibilities include more frequent screening or the introduction of alternative or additional screening modalities (such as ultrasound, magnetic resonance imaging, or digital mammography). Small studies on ultrasound and mammography together suggest that the addition of ultrasound improves sensitivity for women with dense breasts (20,21) but specificity is lower (22). The American College of Radiology Imaging Network study is conducting a randomized controlled trial of combined ultrasound and mammography for women classified by the Breast Imaging-Reporting and Data System classification as having heterogeneously dense or extremely dense breasts (approximately 40% of women ages z40 years; ref.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review concluded that there was insufficient evidence to support the use of any of those 4 methods for population screening. 53 Third, we did not consider the potentially differential effects of changing adjuvant treatment on breast cancer survival among the U.S. and Chinese populations in the model. However, there is no good evidence to assess whether there is differential response to adjuvant treatment by geoethnicity; however, to date, anecdotal experience has failed to identify nonequivalence between the U.S. and Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In a typical examination, a patient is scanned prior to and immediately after the intravenous injection of the contrast agent [Gadolinium-diethylenetriamine pentaacetic acid (DTPA)]. 3Y5 Postcontrast scans are performed repeatedly and the resulting MR image consists of a set of images of parallel tissue slices.…”
Section: Introductionmentioning
confidence: 99%